2005
DOI: 10.1002/jsfa.2188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slope exposure, altitude and yield on coffee quality in two altitude terroirs of Costa Rica, Orosi and Santa María de Dota

Abstract: This study assessed the effects of slope exposure, altitude and yield on several cup quality criteria of coffees from two altitude terroirs of Costa Rica, Orosi (between 1020 and 1250 m above sea level) and Santa María de Dota (between 1550 and 1780 m above sea level). East-facing slopes gave beverages with generally superior attributes, probably owing to better exposure to morning sunlight. These beverages were mainly more acid: at Orosi an acidity score of 2.73 out of 5 was obtained (3.64 for Santa María de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
5
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(207 citation statements)
references
References 11 publications
7
177
5
18
Order By: Relevance
“…On the other hand, Avelino et al (2005) evaluated the quality of coffee beverage of Costa Rica at altitudes between 1,000 and 1,800 m and found that the crops grown in the areas facing East produced coffees with superior quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Avelino et al (2005) evaluated the quality of coffee beverage of Costa Rica at altitudes between 1,000 and 1,800 m and found that the crops grown in the areas facing East produced coffees with superior quality.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also reported the existence of a relationship between altitude and quality of coffee beverage, such as those performed by Guyot et al (1996), Serrano & Castrillón (2002), Decazy et al (2003), Silva et al (2004), Avelino et al (2005) and Dal Molin et al (2008).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The prevalence of high water vapor contents and tropical Land 2018, 7, 4 3 of 13 temperatures leads to a high relative humidity [26,27]. The climatic conditions are favorable for coffee production, and most countries in the region are recognized for their high-quality coffee and shaded coffee systems [28][29][30][31][32], together producing more than 10% of the total global coffee supply [33,34]. However, projections of climate change show that the region is likely to experience severe alterations in climate in the future, which may negatively impact coffee production [35][36][37].…”
Section: Study Regionmentioning
confidence: 99%
“…El factor 2, estuvo conformado principalmente por las variables temperatura ambiente (10,5), humedad relativa (7,8), horas de fermentación (8,1), peso de café lavado (8,6), horas de secado al sol (10,5), porcentaje de merma (10,4), mientras que el factor 3, está representado en su mayoría por las variables aroma (9,3), cuerpo (18,7) y puntaje (18,9). (Tabla 7).…”
Section: El Análisis Clúster Permitió Identificar Tres Grandes Gruposunclassified